Zeitgemäßes Lerndesign zur Professionalisierung von Lehramtsstudierenden im Bereich digital literacy - Lehberger, Regine (Digitalisierung in der Hochschullehre – Perspektiven und Gestaltungsoptionen)
Die Digitalisierung übt tiefgreifenden Einfluss auf verschiedenste Bereiche menschlichen Lebens aus, unter anderem auf Bildung und damit einhergehend auch auf die Hochschullehre. Eine Kultur der Digitalität (Felix Stalder) verändert nicht nur die für Hochschulen grundlegenden Formen der Produktion von Wissen, sondern ebenso die Umgangsformen und Lehr-Lern-Strategien, die in Lehrveranstaltungen zum Einsatz kommen. Sie wirkt sich auf die Art und Weise aus, wie Wissensinhalte und Kompetenzen vermittelt, erworben und angewendet werden, aber auch auf die Integration digitaler Lerninhalte, die Schaffung neuer Lehr- und Lernmethoden sowie neuer Prüfungsformate. Eine Kultur der Digitalität eröffnet Chancen, um die Qualität der Lehre zu verbessern – beispielsweise durch die Erhöhung von Flexibilität, durch Anpassungsmöglichkeiten an die individuellen Bedürfnisse der Studierenden oderdurch die Vorbereitung sowie Ermöglichung lebenslangen Lernens. Damit verbunden sind jedoch auch Herausforderungen, die beispielsweise im Verhältnis und der Orchestrierung von Präsenz- und Online-Phasen, in der technischen Ausstattung oder in der nötigen Professionalität der Dozierenden gründen. Letztlich kommt es darauf an, die Möglichkeiten der Digitalisierung für die Hochschullehre gezielt und sinnvoll zu nutzen, um zu einer Erhöhung der Qualität beizutragen. Dieser Sammelband hat das Ziel zu einer zukunftsweisenden interdisziplinären Entwicklung und sinnvollen Gestaltung einer digitalen Kultur der Lehre beizutragen. Die enthaltenen Beiträge diskutieren allgemeine Rahmungen zur Digitalisierung der Hochschullehre und präsentieren sodann Ausführungen zu digitalen und digital gestützten Formaten verschiedener Größenordnung: von einzelnen Tools, über die Ebene von Lehrveranstaltungen bis hin zur Studienorganisation und flankierenden Maßnahmen.

Einer für Alle? Ein Onlinekurs zur Schulentwicklung im Kontext von Digitalisierung - Lehberger, Regine (Inverted Classroom and beyond 2023: Agile Didaktik für nachhaltige Bildung)

Zum Einfluss von Lehrveranstaltungen mit digitalem Schwerpunkt auf Einstellungen von Lehramtsstudierenden - Lehberger, Regine (Lehrerbildung auf dem Prüfstand)

Umweltethik

Ambivalente Beziehungen. Historische Narrative und Bilder vom Judentum, Christentum und Islam in Bildungsmedien

ENHANCED FINDABILITY AND REUSABILITY OF ENGINEERING DATA BY CONTEXTUAL METADATA - Altun, Osman; Oladazimi, Pooya; Wawer, Max Leo; Raumel, Selina; Wurz, Marc; Barienti, Khemais; Nürnberger, Florian; Lachmayer, Roland; Mozgova, Iryna; Koepler, Oliver; Auer, Sören (Proceedings of the Design Society)
Abstract Complex research problems are increasingly addressed by interdisciplinary, collaborate research projects generating large amounts of heterogeneous amounts of data. The overarching processing, analysis and availability of data are critical success factors for these research efforts. Data repositories enable long term availability of such data for the scientific community. The findability and therefore reusability strongly builds on comprehensive annotations of datasets stored in repositories. Often generic metadata schema are used to annotate data. In this publication we describe the implementation of discipline specific metadata into a data repository to provide more contextual information about data. To avoid extra workload for researchers to provide such metadata a workflow with standardised data templates for automated metadata extraction during the ingest process has been developed. The enriched metadata are in the following used in the development of two repository plugins for data comparison and data visualisation. The added values of discipline-specific annotations and derived search features to support matching and reusable data is then demonstrated by use cases of two Collaborative Research Centres (CRC 1368 and CRC 1153).

Fast 3D Semantic Segmentation Using a Self Attention Network and Random Sampling - Babu, Sandeep; Jegarian, Majid; Fischer, Dirk; Mertsching, Bärbel (Lecture Notes in Computer Science)

"Sterben wollen – Leben müssen – Sterben dürfen? – Gedanken zur Debatte um den assistierten Suizid" (BloKK Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften)

Investigations on Continuous Transient Dynamic Analysis of Clinched Aluminum Sheets - Reschke, Gregor; Brosius, Alexander (Lecture Notes in Production Engineering)

Coming of Age in Umbruchzeiten der ‚alten Bundesrepublik‘, komplementär: Ulrich Woelks „Der Sommer meiner Mutter“ (2019) und Christoph Peters‘ „Dorfroman“ (2020) - Elit, Stefan (Zeitschrift für deutsche Philologie. Sonderheft: Werke im Dialog. (Virtuelle) Begegnungen anlässlich von 40 Jahren Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller)

Lebendige Anschauung auf Abwegen. Komische Kunstbetrachtungen in Ingo Schulzes Band „Tasso im Irrenhaus“ und Frank Witzels Van-Reuningen-Texten - Elit, Stefan (Zeitschrift für deutsche Philologie. Sonderheft: Werke im Dialog. Virtuelle Begegnungen anlässlich von 40 Jahren Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller)

VR zur prospektiven und prozessbezogenen Kompetenzmodellierung (PKOM) im Kontext der digitalen Transformation - Depenbusch, Sarah; Schaper, Niclas; Schumacher, Jan-Philip

Using VR-based animation videos to support business process understanding and learning motivation in SMEs - Depenbusch, Sarah; Schaper, Niclas; Schumacher, Jan-Philip; Schürmann, Mirko

Numerical Investigation of the Coupled Friction Behavior in the Clinching Process Chain - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Ersatzmodellentwicklung zur Berücksichtigung der lokalen Fügeelementkinematik in mechanisch gefügten Verbindungen für die Bauteilauslegung im stahlintensiven Karosseriebau - Bähr, Philipp; Striewe, Marius; Meschut, Gerson; Sommer, Silke; Hein, David (13. Kolloquium: Gemeinsame Forschung in der Mechanischen Fügetechnik)

Conflicting Values in Epidemiological Modelling, Simulation and Dashboard-Design. A Contribution to the Analysis of the Epistemisation of Pandemic Politics - Hälterlein, Jens (Digital Culture & Society)

National, global oder irgendwo dazwischen? Methodische Zugänge zur (neuen) Weltliteratur aus germanistischer Perspektive - Schulte Eickholt, Swen (Der Neue Weltengarten 2022. Jahrbuch für Literatur und Interkulturalität)
Der Artikel untersucht die kulturtheoretische Grundlage eines literaturwissenschaftlichen Zugangs zu Weltliteratur. Dabei setzt er sich mit Theorien des Inter- und Transkulturellem auseinander und macht mit dem methodischen Zugriff des "Doppeltblickens" einen Vorschlag, wie eine interkulturelle Methode vor dem Hintergrund eines komplexen Kulturbegriffs ohne Essentialisierungen gelingen kann.

Relationship between laser-generated micro- and nanostructures and the long-term stability of bonded epoxy-aluminum joints - Freund, Jonathan; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (The Journal of Adhesion)
To improve the mechanical performance and to address current shortcomings of adhesive bonds such as bond degradation due to aging, a pulsed laser surface pretreatment of the metal surfaces of aluminum AW 6082-T6 joints with epoxy adhesive E320 is investigated. The surface treatment of the specimens resulted in increased single-lap shear (SLS) strengths before and after hydrothermal aging in 80°C hot water compared to nonpretreated reference specimens. In order to reveal the correlations of laser parameters, resulting surface morphologies and the SLS strength, differently laser pretreated surfaces were characterized at the micro- and nanoscale using optical and scanning electron microscopies. The surface enlargement was quantified with a digital image analysis of cross-sections prepared from the joint interfaces. An analysis of variances (ANOVA) of the SLS results indicated that the laser parameters power and pulse frequency were most critical for obtaining high SLS strengths. Pretreated joint surfaces with a high micro- and nano-surface enlargement and deep solidification structures provide high SLS strengths of up to 50 MPa and almost negligible aging losses of merely 4%. Undercut structures on the pretreated surfaces were found to be beneficial for the mechanical and aging properties when only limited micro- and nanostructuring was applied.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Transferability of the Structure–Property Relationships from Laser-Pretreated Metal–Polymer Joints to Aluminum–CFRP Hybrid Joints - Freund, Jonathan; Lützenkirchen, Isabel; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (Journal of Composites Science)
The transferability of structure–property relationships for laser-pretreated metal adhesive joints to laser-pretreated metal–carbon-fiber-reinforced plastic (CFRP) bonds was investigated. Single-lap shear tests were performed on hybrid AW 6082-T6–CFRP specimens pretreated with the same pulsed laser surface parameter sets on the metal surface as previously tested, AW 6082-T6–E320 metal adhesive joints. The fracture surfaces were characterized to determine the type of failure and elucidate differences and commonalities in the link between surface structures and single-lap shear strengths. Digital image analyses of the hybrid specimens’ fractured surfaces were used to quantify remaining CFRP fragments on the metallic joint side. The results indicate that high surface enlargements and the presence of undercut structures lead to single-lap shear strengths exceeding 40 MPa and 35 MPa for unaged and aged hybrid specimens, respectively. Whereas for the metal–polymer joints, the trend from high strength to weakly bonded specimens is largely continuous with the degree of surface structuring, hybrid metal–CFRP joints exhibit a drastic drop in joint performance after aging if the laser-generated surface structures are less pronounced with low surface enlargements and crater depths. Surface features and hydrothermal aging determine whether the specimens fail cohesively or adhesively.

Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
A parameter investigation for manufacturing a hybrid system through the prepreg pressing process was carried out within the scope of this work to achieve optimal adhesion properties. The hybrid specimen comprises an aluminium sheet of alloy EN AW 6082 in T6 condition and a thermoset Carbon Fibre Reinforced Plastics prepreg. The prepreg pressing process allows the curing reaction of epoxy resin and the joining process to occur simultaneously to avoid an additional bonding process step. The surface of the aluminium sheet was pretreated in advance using a pulsed Nd:YAG laser to enhance the bonding properties. In the first step, the shear edge tests investigated the adhesion properties achieved with different consolidation (temperature, time and pressure) and laser parameters. Then, 3-point bending tests were carried out to investigate the influence of the consolidation parameters on the mechanical properties of the Carbon Fibre Reinforced Plastics-laminate. In this way, the optimal parameter sets for manufacturing hybrid structures were determined.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry